Development of the Fray-Farthing-Chen Cambridge Process: towards the sustainable production of titanium and its alloys - Hu, Di; Dolganov, Aleksei; Ma, Mingchan; Bhattacharya, Biyash; Bishop, Matthew T.; Chen, George Z. (Springer, 2018)
The Kroll process has been employed for titanium extraction since the 1950s. It is a labour and energy intensive multi-step semi-batch process. The post-extraction processes for making the raw titanium into alloys and products are also excessive, including multiple remelting steps. Invented in the late 1990s, the Fray-Farthing-Chen (FFC) Cambridge process extracts titanium from solid oxides at lower energy consumption via electrochemical reduction in molten salts. Its ability to produce alloys and powders, while retaining the cathode shape also promises energy and material efficient manufacturing. Focusing on titanium and its alloys, this article reviews the recent development of the FFC-Cambridge process in two aspects, (i) resource and process sustainability and (ii) advanced post-extraction processing.